Microwave Sintering of Aluminum-ZrB2 Composite: Focusing on Microstructure and Mechanical Properties - Ghasali,Ehsan (2016)
Abstract Microwave assisted rapid sintering was carried out to fabricate aluminum-ZrB2 metal matrix composites containing 1 wt% cobalt and 10, 15 and 20 wt% ZrB2 as the reinforcements at temperatures of 600, 700 and 800°C. The results showed that the highest values of density and bending strength (97% of theoretical density and 240 MPa, respectively) were obtained in a composite containing 15 wt% ZrB2 and 1 wt% Co sintered at 600°C. Furthermore, the optimum values of compressive strength and hardness (350 MPa and 63 Vickers, respectively) were measured for a composite containing 20 wt% ZrB2 sintered at 600°C. At all sintering temperatures, XRD analysis revealed ZrB2 and aluminum as the only crystalline phases. Microstructure investigations demonstrated a homogeneous distribution of ZrB2 particles in the aluminum matrix.